Barber's neck manipulation causing bilateral diaphragmatic paralysis and type-2 respiratory failure - Ashish Kumar Prakash; Anand Jaiswal; Sandeep Mittal; Poulomi Chatterjee; Sameer Kotalwar; Bornalli Datta (Lung India, 2019)
This is a case report of an unusual cause of bilateral diaphragmatic palsy. A 54-year-old gentleman, presented to us with exertional dyspnea and chest heaviness for the past 6 months which had increased in the last 6 days. Dyspnea increased on lying down. He was diagnosed as pneumonia on the basis of X-ray and chest CT scan, received treatment for the same and responded to the therapy. However, breathlessness and hypercapnia persisted. He had unexplained hypercapnia for which extensive investigations were carried out. Neurological and cardiac assessments were essentially normal. On revisit clinical examination, he was found to have paradoxical diaphragmatic movement with respiration. Ultrasound of chest detected no diaphragmatic movement. Detailed history elicited that patient was fond of neck massage and neck cracking wherein his barber would bend his neck with jerk to either side after a haircut.After considering all possible etiologies; we concluded that it was a case of diaphragm palsy induced by barber neck manipulation, leading to Type-2 respiratory failure. The fact that the vital clues to the diagnosis were elicited by detailed history and thorough examination reinforces that history and clinical examination for doctors shall remain a very important tool for clinical diagnosis.